Notice of Recent Excavations in the Hill Fort of Dunsinane, Perthshire (Proceedings of the Society of Antiquaries of Scotland, 1856)
The legends surrounding the fortress on Dunsinane Hill primarily involve the historical figure of Macbeth and are often mixed up with Shakespeare's fictional character of the same. Excavations on the hill revealed some of the features of the fortification there, the foundations of several rooms and several human skulls along with other bones.